A participatory integrated assessment of the social acceptance of wind energy. (November 2018) - Scherhaufer, Patrick; Höltinger, Stefan; Salak, Boris; Schauppenlehner, Thomas; Schmidt, Johannes
Abstract: This research paper deals with problems of operationalisation or how to conduct research in the field of energy and climate change from a methodological point of view. Guided by a participatory integrated assessment the research project TransWind identified key issues relevant to the social acceptance of wind energy development in Austria. Based on a mixed-method design including modelling and visualisation efforts, workshops, interviews, focus groups and questionnaires researchers and stakeholders expressed their ideas and perceptions with regard to the three dimensions of social acceptance: community, market, and socio-political acceptance. The paper focuses on two main challenges in the assessment: i) the integration of various relevant stakeholders into the research process, ii) the integration of different research methods into one conceptional and methodological reliable assessment investigating the social acceptance of wind energy. The results highlight that there is a strong need for integrating in a systematic way the analytical perspectives of scientists and their approaches with preferences and perceptions of the persons concerned about the issue.